Sharing too much : musings from an unlikely life - Evans, Richard Paul (New York City : Gallery Books, 2024)
"The #1 New York Times bestselling author and "king of Christmas fiction" (The New York Times) delivers a charming and inspirational collection of personal essays.Before he was the #1 New York Times bestselling author of holiday classics such as The Christmas Box, Richard Paul Evans was a young boy being raised by a suicidal mother and dealing with relentless bullying. He could not fathom what the future held for him. Now, in this intimate and heartfelt collection of personal essays, Evans shares his moving journey from childhood to beloved author. With his signature "seasoned finesse" (Booklist), he offers the insightful lessons he's learned and engaging advice about everything from marriage to parenthood and even facing near-death experiences. This is a charming essay collection that is the perfect gift all year round"--
Lessons from childhood -- Faith, Christmas, and miracles -- Short stories and fables -- The author's world -- Random musings -- Unexpected teachers -- Marriage, family, and other blessings -- Acknowledgments.
"Includes the worldwide phenomenon How I Saved My Marriage"--Title page.
Keywords: Evans, Richard Paul -- Anecdotes; Authors, American -- 20th century -- Anecdotes; Christian authors -- United States -- Anecdotes; Essays; Anecdotes